BMSCs Regulate Astrocytes through TSG-6 to Protect the Blood-Brain Barrier after Subarachnoid Hemorrhage - Yilv Wan; Min Song; Xun Xie; Zhen Chen; Ziyun Gao; Xiang Wu; Rui Huang; Min Chen (Mediators of Inflammation)
Background. In patients with subarachnoid hemorrhage (SAH), the damage of the blood-brain barrier (BBB) can be life-threatening. Mesenchymal stem cells are widely used in clinical research due to their pleiotropic properties. This study is aimed at exploring the effect of BMSCs regulating astrocytes on the BBB after SAH. Methods. The SAH model was established by perforating the blood vessels. BMSCs were transfected with TSG-6 inhibitor plasmid and cocultured with astrocytes. Intravenous transplantation of BMSCs was utilized to treat SAH rats. We performed ELISA, neurological scoring, Evans blue staining, NO measurement, immunofluorescence, BBB permeability, Western blot, HE staining, Nissl staining, and immunohistochemistry to evaluate the effect of BMSCs on astrocytes and BBB. Results. SAH rats showed BBB injury, increased BBB permeability, and brain histological damage. BMSCs will secrete TSG-6 after being activated by TNF-α. Under the influence of TSG-6, the NF-κB and MAPK signaling pathways of astrocytes were inhibited. The expression of iNOS was reduced, while occludin, claudin 3, and ZO-1 expression was increased. The production of harmful substances NO and ONOO- decreased. The level of inflammatory factors decreased. The apoptosis of astrocytes was weakened. TSG-6 secreted by BMSCs can relieve inflammation caused by SAH injury. The increase in BBB permeability of SAH rats was further reduced and the risk of rebleeding was reduced. Conclusion. BMSCs can regulate the activation of astrocytes through secreting TSG-6 in vivo and in vitro to protect BBB.